To solve the system of equations using elimination, we start with the two equations:
- \( 3x + 6y = 21 \) (Equation 1)
- \( -5x + 2y = 13 \) (Equation 2)
Step 1: Make the coefficients of y the same.
To do this, we can multiply Equation 2 by 3 to make the coefficient of y in both equations equal:
- \( 3x + 6y = 21 \) (remains the same)
- \( 3(-5x + 2y) = 3(13) \)
\( -15x + 6y = 39 \) (Equation 3)
Now we have the following system of equations:
- \( 3x + 6y = 21 \)
- \( -15x + 6y = 39 \)
Step 2: Eliminate y.
Now we will subtract Equation 1 from Equation 3:
\[ (-15x + 6y) - (3x + 6y) = 39 - 21 \]
This simplifies to:
\[ -15x - 3x + 6y - 6y = 18 \] \[ -18x = 18 \]
Step 3: Solve for x.
Divide both sides by -18:
\[ x = -1 \]
Step 4: Substitute x back to find y.
Now that we have the value of x, we can substitute \( x = -1 \) back into one of the original equations to find y. We can use Equation 1:
\[ 3(-1) + 6y = 21 \] \[ -3 + 6y = 21 \] \[ 6y = 21 + 3 \] \[ 6y = 24 \] \[ y = 4 \]
Step 5: Write the solution.
The solution to the system of equations is:
\[ (x, y) = (-1, 4) \]
So the final answer is:
\[ \boxed{(-1, 4)} \]